TIPOLOGI PERLETAKAN PAPAN IKLAN PADA RUANG JALAN SETURAN - , MUH NUR ADNAN ABBAS; , Ir. M. Santosa, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Seturan street districts included in the administrative area of Depok, Depok subdistrict as it is known that the most rapidly growing region in the province of DIY. There are some private colleges in the area such as street STIE YKPN, Veteran Yogyakarta University, Sanata Dharma University, Atma Jaya Yogyakarta University, STIP INTAN, and ITENAS. The existence of such colleges is the anchor that has implications for the region and growth Seturan Raya as one of the fast growing area in the district of Depok. Unfortunately Seturan Jalan Raya growth is not matched by regional planning that emphasizes the physical elements of the city that resulted in a variety of regional issues such as accessibility and visual pollution areas, strict economic competition along the Seturan Raya street resulted in competition placement billboard on the facade that is not equipped with a control system controlling arrangement of signage in the Street space. Based on this phenomenon, the occurrence of problems in the area along Jalan Raya Seturan the arrangement billboards in areas that obscures the identity of the region caused by the misalignment structuring element signage as part of a design element forming public space. The purpose of this study was to determine the character of the street space Seturan pelingkup and knowing typology placement of billboards on the Seturan Raya Street space. This study used a qualitative approach Rationalistic, which put emphasis on the observation of the physical elements as forming Pelingkup street space, namely the street wall elements, and the roof. The results of this study is intended as a control mechanism mounting billboards along the way so that the character of the area Seturan can be maintained and organized. The results of this study are expected dapata contribute or contribute to relevant stakeholders for the development of knowledge and the design and arrangement of other fast growing regions.